Endoscopic tympanoplasty - Akyigit, Abdulvahap; Sakallıoglu, Oner; Karlidag, Turgut (PLA General Hospital Department of Otolaryngology Head and Neck Surgery, 2017)
Middle ear surgery is usually performed using a surgical microscope. Initially, in otorhinolaryngology practice, endoscopes were used for paranasal sinus surgeries. It was only later that they were applied in the area of otology. In otologic surgeries, endoscopes were first used to visualize the middle ear, before being used to assist with visualization of instruments during cholesteatoma surgeries, although they are still not used alone in various otologic surgeries. As in other surgical fields, there is also a trend towards minimally invasive intervention in the field of otorhinolaryngology. Smaller incisions performed under the guidance of endoscopes are preferred over conventional large incisions. Using this approach, improved outcomes can be achieved and postoperative morbidities can be reduced. In addition, the outcomes of grafts performed using the endoscopic approach are similar to that achieved by the microscopic approach. Therefore, endoscopic ear surgery implementations are becoming increasingly popular. © 2017 PLA General Hospital Department of Otolaryngology Head and Neck Surgery
Keywords: Endoscopic; Myringoplasty; Tympanoplasty